Toll-like receptor ligands induce the expression of interferon-gamma and interleukin-17 in chicken CD4+ T cells - St Paul Michael; Barjesteh Neda; Paolucci Sarah; Pei Yanlong; Sharif Shayan (BMC Research Notes, 2012)
Abstract Background Toll-like receptors (TLRs) are evolutionarily conserved pattern recognition receptors that mediate host responses to pathogens. To date, at least 10 different TLRs have been identified in chickens including TLR2, which binds lipopeptides and other similar ligands such as Pam3CSK4, TLR3, which binds double stranded RNA as well as synthetic molecules such as poly I:C, TLR4, which binds lipopolysaccharide (LPS), and TLR21, which binds CpG DNA motifs. In mammals, TLRs have been detected on CD4+ T cells where they mediate cellular survival, proliferation and the production of cytokines. However, the TLR-mediated responses in chicken CD4+ T cells remain to be determined. As such, the objective of the present study was to elucidate the kinetics of cytokine response to several different TLR ligands in chicken CD4+ T cells. Results The results suggest that these cells express TLRs 2, 3, 4 and 21 at the transcript level, and treatment with ligands for these TLRs significantly influenced the expression of the cytokines interferon (IFN)-γ and interleukin (IL)-17, but not IL-4, IL-10 and IL-13. Specifically, treatment with Pam3CSK4, poly I:C and LPS up-regulated IFN-γ transcripts, while CpG ODN significantly down-regulated them. In contrast, at least one dose of each of the TLR ligands, except for Pam3CSK4, significantly down-regulated IL-17 transcripts. Conclusion Chicken CD4+ T cells respond to ligands for TLRs 2, 3, 4 and 21 by up-regulating or down-regulating cytokine transcripts. Future studies may consider exploring how these TLR ligands may modulate other effector functions in chicken CD4+ T cells, as well as in other T cell subsets such as CD8+ T cells.